Influence of experimental infection by Haemonchus contortus on acetylcholinesterase activity in lymphocytes of lambs - Tonin A.A. (2014)
The aim of this study was to evaluate the acetylcholinesterase (AChE) activity in lymphocytes of lambs experimentally infected by Haemonchus contortus. A total of 14 healthy lambs were used, divided into two groups of seven animals each. Group A (negative control) represented the uninfected animals, and Group B (positive control) was formed by animals infected with 15,000 larvae of H. contortus. Blood was drawn on the days 15, 45 and 75 post-infection (PI) in order to perform the white blood cells (WBC) count, as well as the evaluation of AChE activity in lymphocytes. Parasitological stool exam (eggs per gram of feces - EPG) was performed on the same days to follow up the evolution of the infection. On day 15 PI it was verified negative EPG; however, on days 45 and 75 PI it was observed positive EPG only in the animals of group B. In the three evaluated periods was observed a lower number of leukocytes, associated with decreased lymphocytes and neutrophils in lambs infected by this gastrointestinal nematodes. Lambs infected with H. contortus showed significant (P<. 0.01) lower AChE activity in lymphocytes compared uninfected. Statistically, there was a positive correlation (P<. 0.05) between AChE activity in lymphocytes and number of lymphocytes (r= 0.69). The lymphocytes are cells with direct participation in the cholinergic system; therefore, based on these results, it can be concluded that the experimental infection with H. contortus influences the number of lymphocytes, and consequently the AChE activity in these cells. © 2014 Elsevier Inc.